2007
DOI: 10.1126/science.1140462
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Histories and Patterns of Linkage Disequilibrium in Chinese and Indian Rhesus Macaques

Abstract: mosome inactivation in females (25, 26). In addition, retrotransposons provide highly valuable genetic systems for primate population and phylogenetic studies, because they have a known ancestral (i.e., insertion-absent) state, and the chance that the same type of element would integrate at precisely the same location in multiple individuals is essentially zero (i.e., the insertions are identical by descent) (27, 28). Altogether, understanding the mobile-element landscape in primates is not only important for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
187
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(209 citation statements)
references
References 15 publications
19
187
3
Order By: Relevance
“…Therefore, unsorted ancestral polymorphisms could not entirely explain the high proportion of inconsistent regions observed between the CE macaque and CR macaque. Furthermore, by combining previous single nucleotide polymorphism (SNP) data from IR and CR macaque populations with data from our own sequenced CR and CE macaque individuals 8 , we noted that our CE macaque individual clustered within the CR macaque population (Supplementary Section 4). This supports the occurrence of strong gene flow from the CR to the CE macaque genome.…”
Section: E T T E R Smentioning
confidence: 75%
“…Therefore, unsorted ancestral polymorphisms could not entirely explain the high proportion of inconsistent regions observed between the CE macaque and CR macaque. Furthermore, by combining previous single nucleotide polymorphism (SNP) data from IR and CR macaque populations with data from our own sequenced CR and CE macaque individuals 8 , we noted that our CE macaque individual clustered within the CR macaque population (Supplementary Section 4). This supports the occurrence of strong gene flow from the CR to the CE macaque genome.…”
Section: E T T E R Smentioning
confidence: 75%
“…Indeed, HRI is thought to play a fundamental role in shaping the evolution of recombination rates in small effective populations, such as those found in these three primate species (Stone and Verrelli 2006;Hernandez et al 2007), as modifier alleles that increase recombination locally can be selected if they reduce HRI (Felsenstein 1974;Felsenstein and Yokoyama 1976;Otto and Lenormand 2002;Barton and Otto 2005). Intuitively, this phenomenon occurs because a modifier allele produces, and so resides on, haplotypes with greater fitness (e.g., with fewer deleterious or more advantageous mutations) and as a result tends to hitchhike to fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations by Andrade et al (2004), Doxiadis et al (2003Doxiadis et al ( , 2006, Ferguson et al (2007), Hernandez et al (2007), Smith (1998, 2004), Kanthaswamy et al (2006), Malhi et al (2007), Morin et al (1997), Penedo et al (2005), Satkoski et al (2007), and Viray et al (2001) have all characterized the genetic composition of rhesus macaque populations in the wild and in captivity. Most of these studies have reported discrete genetic differences between Indian and Chinese rhesus macaques and much greater genetic heterogeneity and substructuring in the latter than in the former.…”
Section: Introductionmentioning
confidence: 99%